2011
DOI: 10.1021/la202983d
|View full text |Cite
|
Sign up to set email alerts
|

Morphology-Dependent Voltage Sensitivity of a Gold Nanostructure

Abstract: Gold nanostructures of various morphologies, including nanospheres, nanorods, nanoprisms, and thin films, were immobilized on ITO-coated coverslips in order to investigate the response of their scattering to potential. Shifts in the plasmon band obtained by potential-modulated spectroscopic imaging indicated that the voltage sensitivity of the gold nanostructure is dependent on its morphology, with nanospheres exhibiting the lowest sensitivity and ultrathin gold films exhibiting the highest. The effects of pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 35 publications
2
25
0
5
Order By: Relevance
“… 18 29 Chemically prepared nanoparticles are inherently heterogeneous in size and shape even under identical growth conditions, leading to heterogeneity in catalytic and electrochemical activity within nanoparticle populations. 3 , 7 , 8 , 30 , 31 Additionally, surface defect sites have been shown to increase nanocatalyst activity. 32 , 33 The synthesis of nanocatalysts has historically relied heavily on iterative trial and error optimization schemes.…”
Section: Introductionmentioning
confidence: 99%
“… 18 29 Chemically prepared nanoparticles are inherently heterogeneous in size and shape even under identical growth conditions, leading to heterogeneity in catalytic and electrochemical activity within nanoparticle populations. 3 , 7 , 8 , 30 , 31 Additionally, surface defect sites have been shown to increase nanocatalyst activity. 32 , 33 The synthesis of nanocatalysts has historically relied heavily on iterative trial and error optimization schemes.…”
Section: Introductionmentioning
confidence: 99%
“…The resonance wavelength shift linearly scales with the applied potential, whereas the switching speed is dominated by the "RC" charging time of the EDL. A key demonstration of non-Faradaic charging effects was reported by Huang et al [202,206]. In their experiments, they demonstrated that the scattering efficiency of PNAs can be modulated through non-Faradaic charging processes using an external electrode.…”
Section: Electrical Gatingmentioning
confidence: 88%
“…Compared to electrical biasing in a dielectric medium, electrical gating within an ionic medium (i.e., liquid-or solid-state electrolyte solution) can lead to stronger LSPR modulations [199,200]. Plasmonic response in ionic media can be tuned through non-Faradaic [201,202] and Faradaic [203][204][205] charging effects. In non-Faradaic processes, application of an electrical potential difference between a PNA and a reference electrode results in the formation of an atomic scale (∼Å) electrical double layer (EDL) on the nanostructure surface.…”
Section: Electrical Gatingmentioning
confidence: 99%
“…The plasmon resonance of metal nanostructures can also be modulated by applying an external electrostatic field to alter their free electron density . For instance, increasing the free electron density in a metal nanostructure leads to a stronger electron oscillation and induces a blue shift in the plasmon resonance wavelength, leading to red shift and damping of the plasmonic band to make reversible switches . However, the aforementioned strategies only yield switches of relatively low sensitivity (ON/OFF ratio <5), which present a formidable challenge for practical applications of active plasmonic switch devices.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37][38] For instance, increasing the free electron density in a metal nanostructure leads to a stronger electron oscillation and induces a blue shift in the plasmon resonance wavelength, leading to red shift and damping of the plasmonic band to make reversible switches. [39][40][41] However, the aforementioned strategies only yield switches of relatively low sensitivity (ON/OFF ratio <5), which present a formidable challenge for practical applications of active plasmonic switch devices.As we know, surface-enhanced Raman spectroscopy (SERS) is a well-established spectroscopic technique for ultrasensitive sensing and probing the plasmonic responses of metal nanoparticles. [42][43][44][45] The effectiveness of the technique is due to the fact that the intensity of the plasmon resonance peak is related to electric fi eld ( E ) of plasmonic nanoparticles and the enhancement of the Raman signal is proportional to E 4 , thus inducing a dramatic response.…”
mentioning
confidence: 99%